Engineering multi-specific antibodies against HIV-1 - Neal N. Padte; Jian Yu; Yaoxing Huang; David D. Ho (Retrovirology, 2018)
Abstract As increasing numbers of broadly neutralizing monoclonal antibodies (mAbs) against HIV-1 enter clinical trials, it is becoming evident that combinations of mAbs are necessary to block infection by the diverse array of globally circulating HIV-1 strains and to limit the emergence of resistant viruses. Multi-specific antibodies, in which two or more HIV-1 entry-targeting moieties are engineered into a single molecule, have expanded rapidly in recent years and offer an attractive solution that can improve neutralization breadth and erect a higher barrier against viral resistance. In some unique cases, multi-specific HIV-1 antibodies have demonstrated vastly improved antiviral potency due to increased avidity or enhanced spatiotemporal functional activity. This review will describe the recent advancements in the HIV-1 field in engineering monoclonal, bispecific and trispecific antibodies with enhanced breadth and potency against HIV-1. A case study will also be presented as an example of the developmental challenges these multi-specific antibodies may face on their path to the clinic. The tremendous potential of multi-specific antibodies against the HIV-1 epidemic is readily evident. Creativity in their discovery and engineering, and acumen during their development, will be the true determinant of their success in reducing HIV-1 infection and disease.